Investigation of post seismic deformation in Karlıova (Turkey) inferred from InSAR analysis - Horasan, Koray. (Thesis (M.S.) - Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2013., 2013)
Interferometric Synthetic Aperture Radar is a new technique used in investigating the deformations occurring on the earth surface. By its capability of providing much broader domain coverage as compared to any other available techniques, geologists are using the interferometric synthetic aperture radar technique in many areas of their research and primarily crustal deformation. The purpose of this study is to observe the post-seismic impacts using the interferometry technique. In line with this purpose, the effects of deformations resulting from post-seismic impacts of earthquakes have been analyzed with the interferometric synthetic aperture radar technique. The region Karlıova was chosen as the study area. Karlıova-Bingöl-Erzincan triangle is located in the junction of the two most important transform faults: the North Anatolian Fault (NAF) and the East Anatolian Fault (EAF). The area between that two transform faults is a place where KDGB and KB-GD trending cross-fault systems is developed. Therefore, it is the region of the highest concentrations of the active faults in Turkey. The earthquakes that occurred in this region between 2005-2008 were examined in detail. With this study using the InSAR technique, for two separate earthquakes (10.12.2005 Mw=5.2 Depth:18 km and 26.08.2007 Mw=5.1 Depth:5km), a deformation in the direction of the satellite view of 56 mm during 2005-2006 and 140 mm during 2006-2008 has been determined respectively. In the interferograms generated by using the radar images in the C-band, one fringe theoretically corresponds to a deformation of half the radar wavelength. Therefore, deformations less than 28 mm in the area cannot be determined by the InSAR technique. The SAR data differ from the GPS data in time. During this time range, 17 earthquakes of moderate magnitude have also occurred in the area. The results differ from each other significantly since InSAR measurements contain post-seismic deformation while GPS observations do not. The spatial density of GPS sites is limited. Moreover, noisy interferograms due to atmospheric signal, and phase unwrapping errors affects the accuracy assessment and interpretation of the results.
Keywords: Earthquakes -- Karlıova -- Turkey.; Seismology -- Data processing.; Earthquakes -- Computer simulation.; Seismology -- Statistical methods.